CONTROL BODY COORDINATION MODEL IN THE PROCESS OF RESPONSE TO LARGE-SCALE EMERGENCIES - Liashenko, O. M. (Science and Transport Progress, 2017)
Purpose. The article is devoted to developing the control body coordination model in the process of response to large-scale emergencies. Methodology. Research methods include a mathematical apparatus of the theory of hierarchical multi-level systems, predicate logic, as well as the principles of centralized management, which imply the existence of a single coordination control center in the case of occurrence of large-scale emergencies, which would determine basic rules of cooperation between control bodies, as well as the manpower and resources of the Civil Defense of Ukraine when implementing tactical action plans for the localization and recovery of emergency consequences. Findings. Based on the devised model, we propose an approach to solving the task of coordination between control bodies in the process of response to large-scale emergencies under conditions of uncertainty and incomplete information, as well as time constraints for making managerial decisions. The specifics of the model is in the use of mathematical apparatus of the theory of hierarchical multi-level systems and predicate logic in order to implement the procedures of coordination of three types of objectives, formally described by three types of tasks: 1) a global task whose solution is aimed at achieving a common global objective of the system, specifically, to minimize the consequences of emergencies; 2) a task of coordinating control body, the solving of which achieves a coordinated functioning of specialized rescue units and squads during implementation of a set of measures to liquidate consequences in the area of emergencies; 3) local tasks for control bodies over the response to emergencies, solving which aims at achieving a common global objective of the system. Originality. We proposed for the first time a structure of the hierarchical multi-level system for coordination between control bodies in the process of response to large-scale emergencies. The levels of system management are determined. The approach is proposed to solving a task of the coordination between control bodies under conditions of uncertainty and incomplete information. Coordination is ensured through the procedures of coordinating goals and tasks solved at different levels in the hierarchy of the considered system, under conditions of centralized management and the originality of emerging management situations. Practical value. Results of the present work might be applied in the tasks of coordinating management and decision-making in hierarchical multi-level systems of civil protection of population and territories from emergencies.